ANALISIS PENGARUH KURS DAN SUKU BUNGA BI RATE TERHADAP EKSPOR PERTANIAN INDONESIA KE AMERIKA SERIKAT - Suprianto '; Syapsan '; Darmayuda ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research was conducted by analyzing data of agricultural export value of Indonesia to the United States, data exchange and data SBI. The data used is secondary data that is time series selama10 year. Methods of data analysis used in this study is the Ordinary Last Square (OLS) with a multiple linear regression model with tools arithmetic program SPSS, based on the regression calculation using SPSS 20 obtained R2 value of 76% indicates that the variation in the value of agricultural exports Indonesia to America Tuft is able to be explained simultaneously by variable-rate variable (X1) and interest rate (X2) by 76%, whiletheremaining24%,Regression coefficient value of variable rate (X1) positive and significant impact on Indonesia's agricultural exports to the United States. Regression coefficient value for a variable rate which is equal to 668, meaning that if there is an increase of 1.00 dollar exchange rate, the value of Indonesia's agricultural exports to the United States have kenaikansebesar USD 668. coefficient value X2 (SBI) is approximately -.482 that the BI rate negative effect and significant impact on the value of Indonesia's agricultural exports to the United States, meaning that a 1% increase in interest rates, will lower the level of Indonesia's agricultural exports to the US amounted to USD 482.Keywords: Exchange, SBI, Indonesia Agricultural Export To Americ